(untitled) (Ciudades, 2025)
The objective of this research is to estimate the effects of residential segregation by social class on housing supply prices. Social class segregation indexes linked to the area of residence of households are used as explanatory variables of price, and parameters are estimated by the Geographically Weighted Regression method. The effects of segregation are not evenly distributed in the urban residential space and, as a general feature, the price of upper and middle-class housing increases with segregation, while that of lower class housing decreases